Primary school children’s perspectives on common diseases and medicines used: implications for school healthcare programmes and priority setting in Uganda - Akello, Grace; Reis, Ria; Ovuga, Emilio; Rwabukwali, Charles B.; Kabonesa, Consolata; Richters, Annemiek (African health sciences, 2007)
Existing school health programmes in Uganda target children above five years for de-worming, oral hygiene and frequent vaccination of girls of reproductive age. Objective: To assess primary school children’s perspectives on common diseases they experience and medicines used in order to suggest reforms for school healthcare programmes and priority setting. Methods: Rapid appraisal approaches, triangulated with a survey, using a semi-structured questionnaire with 80 children aged 8-15 years, were used in data collection. This was done during a three months fieldwork in one primary boarding school in Kampala. An investigation was made into perspectives of children on their recent illness experiences and medicines they used to recover. Other techniques in data collection included participant observation and eliciting children’s narratives of diseases they experienced in a two weeks recall. Key informants, who included school teachers, a nurse, 2 paediatricians, 4 matrons and private health service providers in the vicinity of the school, were approached to validate children’s narratives. Results: Children named and ranked malaria as the most severe and frequently experienced disease. Other diseases mentioned included diarrhoea, skin fungal infections, flu, and typhoid. The symptoms children recognised in case of illness were high body temperature, vomiting, headache, weakness, appetite loss and diarrhoea. Children were either given medicines by the school nurse or they selfmedicated using pharmaceuticals including chloroquine, panadol, flagyl, fansidar, quinine injections, capsules (amoxicillin and ampicillin) obtained from the clinics, drug shops, pharmacies, and other unspecified indigenous medicines from their home and markets. Conclusion: The healthcare needs and priorities of children in primary school are infectious diseases which they could readily identify.
Keywords: Children; Illnesses; School healthcare programmes; Priority setting; Uganda